Socio-economic Factors and Residents’ Motivation for Travel - A Conceptual Study - Kanta Minj, Shashi; Mohan Mishra, Jitendra (Atna Journal of Tourism Studies, 2021)
There are several factors which influence the travel attitude of residents in choosing a destination. In tourism research, many researchers have examined social, cultural, economic, psychological, personal, internal and external factors that influence the travel attitudes of residents. This paper attempts to conceptualise the socio-economic factors such as income, education, and health that influence the residents‟ motivation for travel. The study concludes with a conceptual model indicating the interaction between the socio-economic factors and the residents‟ motivation/ constraints for travel that can be studied in future using an empirical model.